Cardiovascular Profile and Cardiovascular Imaging After Bariatric Surgery: A Narrative Review - Mihaela Toader; Liliana Gheorghe; Costin Chirica; Ionuț-Alexandru Ghicu; Sabina-Ioana Chirica; Andreea Isabela Mazga; Danisia Haba; Mădălina Maxim; Ancuța Andreea Miler; Daniela Crișu; Mihai Ștefan Cristian Haba; Daniel Vasile Timofte (Medicina)
Background and Objectives: Up until now, behavioral interventions and pharmacological therapies were the main approach available for the management of obesity. Diet and exercise, when used as a singular therapeutic method, are inadequate for a successful outcome. Research shows promising results for the surgical treatment of obesity, especially in the area of bariatric surgery (BaS). The relevance of this study is the valuable analysis of the evolution of obese patients with increased cardiovascular risk. Materials and Methods: The patients eligible for BaS commonly suffer from multiple chronic conditions, including type 2 diabetes, obstructive sleep apnea, cardiovascular diseases, and non-alcoholic fatty liver disease. Additionally, obesity contributes to an increased probability of developing certain types of cancer, osteoarthritis, urinary incontinence, and chronic kidney disease. In this review, we focused especially on the cardiovascular status of obese patients who underwent bariatric procedures. Results: BaS has been found to be strongly associated with a reduced incidence of severe complications in individuals with a history of myocardial infarction (MI) and severe obesity. Specifically, this procedure is linked to a lower occurrence of major adverse cardiovascular events and a decrease in overall mortality. Also, BaS is correlated with a reduced risk of recurrent MI and the development of new-onset heart failure. Conclusions: The results of BaS involve a significant amelioration of the BMI, contributing to a considerable decrease in cardiovascular risk factors and to a notable refinement in the cardiovascular structure and function.